The response of soil solution chemistry in European forests to decreasing acid deposition. (3rd May 2018) - Johnson, James; Graf Pannatier, Elisabeth; Carnicelli, Stefano; Cecchini, Guia; Clarke, Nicholas; Cools, Nathalie; Hansen, Karin; Meesenburg, Henning; Nieminen, Tiina M.; Pihl‐Karlsson, Gunilla; Titeux, Hugues; Vanguelova, Elena; et al.
Abstract: Acid deposition arising from sulphur (S) and nitrogen (N) emissions from fossil fuel combustion and agriculture has contributed to the acidification of terrestrial ecosystems in many regions globally. However, in Europe and North America, S deposition has greatly decreased in recent decades due to emissions controls. In this study, we assessed the response of soil solution chemistry in mineral horizons of European forests to these changes. Trends in pH, acid neutralizing capacity (ANC), major ions, total aluminium (Altot ) and dissolved organic carbon were determined for the period 1995–2012. Plots with at least 10 years of observations from the ICP Forests monitoring network were used. Trends were assessed for the upper mineral soil (10–20 cm, 104 plots) and subsoil (40–80 cm, 162 plots). There was a large decrease in the concentration of sulphate ( SO 4 2 − ) in soil solution; over a 10‐year period (2000–2010), SO 4 2 − decreased by 52% at 10–20 cm and 40% at 40–80 cm. Nitrate was unchanged at 10–20 cm but decreased at 40–80 cm. The decrease in acid anions was accompanied by a large and significant decrease in the concentration of the nutrient base cations: calcium, magnesium and potassium (Bc = Ca 2+  + Mg 2+  + K + ) and Altot over the entire dataset. The response of soil solution acidity was nonuniform. At 10–20 cm, ANC increased in acid‐sensitive soils (base saturation ≤10%) indicating a recovery, but ANC decreased in soils with base saturation >10%. At 40–80 cm, ANC remained unchanged in acid‐sensitive soils (base saturation ≤20%, pH CaCl 2  ≤ 4.5) and decreased in better‐buffered soils (base saturation >20%, pH CaCl 2  > 4.5). In addition, the molar ratio of Bc to Altot either did not change or decreased. The results suggest a long‐time lag between emission abatement and changes in soil solution acidity and underline the importance of long‐term monitoring in evaluating ecosystem response to decreases in deposition. Abstract :